Wisma AmFirst, Kelana Jaya - Mohamad Rostan@Rostam, Mohamad Alif Rusyaidi; Yusop, Muhammad Syafiq; Mohd Yasin, Muhammad Nur Aliff; Mohamad Nasir, Nur Aina Nadzirah (2024)
Wisma Amfirst, Kelana Jaya is located within SS7, Kelana Jaya which is accessible from Kuala Lumpur City Centre from the North Klang Valley Expressway (NKVE), Lebuhraya Damansara (LDP) and the Federal Highway. The surrounding area has a diverse range of architectural styles and includes shopping centres, apartments and condominiums, purpose-built detached homes, office, and commercial buildings. The Kelana Jaya Recreational Park and The MBPJ Stadium are prominent landmarks in the immediate surroundings. The general information about The Wisma Amfirst, Kelana Jaya is the building itself has two towers that operates as an office building. The building consists about 16-storey office building comprising of two towers, a 5-storey podium block, one car park basement and one cafeteria. The building was completed in year 2001, managed by one of the best property management Savills (KL) Sdn Bhd.